Production and Characterization of Nanoparticle Based Hyaluronate Gel Containing Retinyl Palmitate for Wound Healing - Esposito, Elisabetta; Pecorelli, Alessandra; Sguizzato, Maddalena; Drechsler, Markus; Mariani, Paolo; Carducci, Federica; Cervellati, Franco; Nastruzzi, Claudio; Cortesi, Rita; Valacchi, Giuseppe (Current Drug Delivery, 2018)
Background: Wound healing is a biological process that can get in a state of pathologic inflammation, requiring the use of specific medications able to promote proper tissue repair. Objective: The study describes the production and characterization of nanoparticle based gel for wound healing treatment designed to deliver hyaluronic acid and retinyl palmitate onto the skin. Methods: Tristearin solid lipid nanoparticles and nanostructured lipid carriers based on a tristearin and caprylic/capric triglyceride mixture were produced and characterized. Gel spreadability and viscosity were investigated. Drug diffusion and “in vitro” wound healing were assessed by Franz cell and scratch wound assay in keratinocytes. Results: Cryogenic transmission electron microscopy evidenced flat discoid nanoparticles. Photon correlation spectroscopy analysis indicated homogeneous dimensional distribution and mean diameter 132±46 nm. X-ray evidenced a lamellar inner structure of lipid nanoparticles. Nanostructured lipid carriers, being based on a heterogeneous solid/ liquid lipid mixture, could better solubilize retinyl palmitate and control its stability. The hyaluronic acid directly added into nanoparticles' dispersion enabled to obtain a shear-thinning gel suitable for cutaneous administration. Retynil palmitate diffusion was slower from the nanoparticulate gel with respect to the plain nanoparticle dispersion. The “wound healing” effect of nanoparticulate gel containing retinyl palmitate and hyaluronic acid, analyzed in HaCaT cells, showed significant differences in wounded areas between treated and control cells during the first 24 h postwounding suggesting a synergic effect of retinyl palmitate and hyaluronic acid in “in vitro” wound healing. Conclusions: This study suggests that a nanoparticle based hyaluronate gel containing retinyl palmitate can be efficiently used for wound healing.
Keywords: cryogenic